The Use Of Digital Technologies In Support Of The State's Economy (Pedagogical Cluster-Journal of Pedagogical Developments, 2024)
The development of digital technologies leads to the emergence of new opportunities for the organization of the educational process. The article discusses the main directions of digital transformation in the economy. It is shown that digital technologies for the economic process are a necessary but insufficient condition for improving the effectiveness of educational work. As a result of the analysis, the prospects and possibilities of the consequences of the transformation of the modern economy have been developed, the main directions of the introduction of digital technologies of the economic process based on the use of digital technologies have been identified.